Recombinant Resilin‐Based Bioelastomers for Regenerative Medicine Applications. Issue 2 (3rd December 2015) - Li, Linqing; Mahara, Atsushi; Tong, Zhixiang; Levenson, Eric A.; McGann, Christopher L.; Jia, Xinqiao; Yamaoka, Tetsuji; Kiick, Kristi L.
Abstract : The outstanding elasticity, excellent resilience at high‐frequency, and hydrophilic capacity of natural resilin have motivated investigations of recombinant resilin‐based biomaterials as a new class of bio‐elastomers in the engineering of mechanically active tissues. Accordingly, here the comprehensive characterization of modular resilin‐like polypeptide (RLP) hydrogels is presented and their suitability as a novel biomaterial for in vivo applications is introduced. Oscillatory rheology confirmed that a full suite of the RLPs can be rapidly cross‐linked upon addition of the tris(hydroxymethyl phosphine) cross‐linker, achieving similar in situ shear storage moduli (20 k ± 3.5 Pa) across various material compositions. Uniaxial stress relaxation tensile testing of hydrated RLP hydrogels under cyclic loading and unloading showed negligible stress reduction and hysteresis, superior reversible extensibility, and high resilience with Young's moduli of 30 ± 7.4 kPa. RLP hydrogels containing MMP‐sensitive domains are susceptible to enzymatic degradation by matrix metalloproteinase‐1 (MMP‐1). Cell culture studies revealed that RLP‐based hydrogels supported the attachment and spreading (2D) of human mesenchymal stem cells and did not activate cultured macrophages. Subcutaneous transplantation of RLP hydrogels in a rat model, which to our knowledge is the first such reported in vivo analysis of RLP‐based hydrogels, illustrated that these materials do not elicit a significant inflammatory response, suggesting their potential as materials for tissue engineering applications with targets of mechanically demanding tissues such as vocal fold and cardiovascular tissues. Abstract : Resilin‐like polypeptide‐based hydrogels, a new class of elastomeric materials with modular design features, exhibit excellent mechanical properties, tunable enzymatic‐mediated biodegradation, biological function as well as promising in vitro cytocompatibility and in vivo biocompatibility, demonstrating their potential in the engineering of mechanically active tissues.